Level Set and PDE Based Reconstruction Methods in Imaging Cetraro, Italy 2008, Editors: Martin Burger, Stanley Osher - Burger, Martin; Mennucci, Andrea C.G.; Osher, Stanley; Rumpf, Martin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
This book takes readers on a tour through modern methods in image analysis and reconstruction based on level set and PDE techniques, the major focus being on morphological and geometric structures in images. The aspects covered include edge-sharpening image reconstruction and denoising, segmentation and shape analysis in images, and image matching. For each, the lecture notes provide insights into the basic analysis of modern variational and PDE-based techniques, as well as computational aspects and applications.
A Guide to the TV Zoo -- EM-TV methods for inverse problems with Poisson noise -- Variational Methods in Image Matching and Motion Extraction -- Metrics of Curves in Shape Optimization and Analysis.
Keywords: Mathematics; Computer vision; Differential equations, partial; Computer science -- Mathematics; Mathematics; Partial Differential Equations; Computational Mathematics and Numerical Analysis; Image Processing and Computer Vision